CONSTITUTIONAL PROTECTION AGAINST UNEQUAL REMUNERATION IN INDIA - Jyoti Pawar; Dr. Umar Jahan (International Journal of Data Science and IoT Management System, 2023)
Equalization of pay is one of the main principles of Indian Constitution to maintain the justice and equity in the work place. Wage differences on the basis of gender, caste, and other discriminatory dysfunctions remain prevalent in the sectors throughout India even though safeguarded by the constitutional provisions. The paper examines the provisions of the Constitution, court interventions and modern problems with providing equal pay. The paper conducts descriptive statistics and hypothesis testing in its attempt to address the up-to-date situation of wage equality and also challenge the efficiency of the measures provided by the constitution. The paper ends with policy changes suggestions, as well as measures to deal with wage inequality through tighter enforcement.